2015
DOI: 10.4110/in.2015.15.6.291
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-inflammatory Effect of GV1001 Mediated by the Downregulation of ENO1-induced Pro-inflammatory Cytokine Production

Abstract: GV1001 is a peptide derived from the human telomerase reverse transcriptase (hTERT) sequence that is reported to have anti-cancer and anti-inflammatory effects. Enolase1 (ENO1) is a glycolytic enzyme, and stimulation of this enzyme induces high levels of pro-inflammatory cytokines from concanavalin A (Con A)-activated peripheral blood mononuclear cells (PBMCs) and ENO1-expressing monocytes in healthy subjects, as well as from macrophages in rheumatoid arthritis (RA) patients. Therefore, this study investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…GV1001, a novel cell-penetrating peptide (16-amino-acid sequence) derived from human telomerase reverse transcriptase, has been implicated to have anticancer, antioxidant, anti-inflammatory, and antiapoptotic effects in kidney; it prevents myocardial ischemia-reperfusion injury; stimulates neural stem cell; and is active against various cancer types [7][8][9][10][11]. Moreover, our previous studies revealed that GV1001 significantly attenuated hearing threshold shift and cochlear outer hair cell (OHC) damage in kanamycin-induced ototoxicity mouse model [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…GV1001, a novel cell-penetrating peptide (16-amino-acid sequence) derived from human telomerase reverse transcriptase, has been implicated to have anticancer, antioxidant, anti-inflammatory, and antiapoptotic effects in kidney; it prevents myocardial ischemia-reperfusion injury; stimulates neural stem cell; and is active against various cancer types [7][8][9][10][11]. Moreover, our previous studies revealed that GV1001 significantly attenuated hearing threshold shift and cochlear outer hair cell (OHC) damage in kanamycin-induced ototoxicity mouse model [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Among these immune cells, the macrophage is one of the major effector cells governing inflammatory responses by producing various inflammatory mediators, including nitric oxide (NO), reactive oxygen/nitrogen species (ROS/RNS), prostaglandin E 2 (PGE 2 ), and different types of proinflammatory cytokines. The latter include tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6 [under the control of the activator protein (AP)-1], nuclear factor kappa B (NF-κB), and interferon (IFN) regulatory factor 3 (IRF3) [2] , [3] , [4] , [5] , [6] , [7] . Although inflammation is a host defense mechanism to protect the body from invading pathogens, chronic inflammation, which is a prolonged state affecting tissue remodeling for several weeks to years, is regarded as a leading cause in the development of a variety of diseases, such as inflammatory/autoimmune diseases, neurodegenerative diseases, and cancers [8] , [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%
“…ENO1 is known to induce inflammation through activation of the p38 MAPK and NF-κB signaling pathways [37]. Besides this, it is an effective inhibitor that downregulates the production of pro-inflammatory cytokines through the suppression of p38 MAPK and NF-κB activation following ENO1 stimulation [38]. It has also been observed that hypoxia significantly increases glucose uptake and that glucose transporter (GLUT) 1 and 3 expression are upregulated under hypoxia.…”
Section: Discussionmentioning
confidence: 99%